PSYCHOLOGICAL FOUNDATIONS OF PROFESSIONAL ORIENTATION IN FUTURE EDUCATORS (Web of Teachers: Inderscience Research, 2025)
This article analyzes the psychological foundations of professional orientation in future educators. Professional orientation in the teaching profession is associated with an individual's professional motivation, interests, abilities, and psychological readiness, and its formation is influenced by various factors. The article explores the concept of professional orientation, its psychological criteria, stages of development, and the factors affecting its formation. Additionally, methods for developing professional preparedness and professional identity in future educators are examined. The findings of the article conclude with recommendations aimed at improving the pedagogical education process.